1963
DOI: 10.1136/bmj.2.5367.1226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pronethalol in Angina Pectoris

Abstract: The problem of assessing the numerous new drugs offered to clinicians is continuously increasing. It is not always possible, even if desirable, to mount a substantial and definitive therapeutic trial for each new drug in a single department. In these circumstances close observation of a few patients in several centres may provide data adequate to justify more general distribution of a new drug, with minimal diversion of workers from their other tasks. The animal pharmacology of a new adrenergic beta-receptor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
2

Year Published

1965
1965
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(16 citation statements)
references
References 3 publications
1
13
0
2
Order By: Relevance
“…While tremors and convulsions have not been described in man, effective doses are often associated with unpleasant subjective side-effects. Mild disorientation, slight inco-ordination, nausea and vomiting have been described (Alleyne et al, 1963). Since the toxic signs in animals are seen with the inactive (+)-isomer as as well as with the active (-)-isomers (Howe, 1963), it has been assumed that the effects of pronethalol on the central nervous system are probably not due to 8l-receptor blockade.…”
mentioning
confidence: 99%
“…While tremors and convulsions have not been described in man, effective doses are often associated with unpleasant subjective side-effects. Mild disorientation, slight inco-ordination, nausea and vomiting have been described (Alleyne et al, 1963). Since the toxic signs in animals are seen with the inactive (+)-isomer as as well as with the active (-)-isomers (Howe, 1963), it has been assumed that the effects of pronethalol on the central nervous system are probably not due to 8l-receptor blockade.…”
mentioning
confidence: 99%
“…It was introduced into clinical trial specifically to determine whether an agent which prevented the action of catecholamines on the heart would be of benefit in angina pectoris (Black & Stephenson, 1962). It was shown to increase exercise tolerance in angina pectoris, and also to improve the anginal state clinically (Dornhorst & Robinson, 1962;Alleyne et al, 1963) Subsequently, pronethalol was withdrawn because it was found to cause lymphomata in the thymus of certain strains of mice. It was replaced by propranolol ('Inderal', ICI) which has a different chemical structure and is more potent (Black, Duncan & Shanks, 1965).…”
Section: Subsequent Developmentsmentioning
confidence: 99%
“…loth these drugs have been used in the treatment of angina toris, but the reports on their value have been conflicting. double-blind trials favourable results were obtained with nethalol by Alleyne et al (1963) and with propranolol by lan (1965), whereas Srivastava et al (1964) found proiolol to have little advantage over placebo. Tests involving oducible exercise have also been used to assess the value the drugs in angina.…”
Section: Beta-adrenergic Blockade In Angina Pectorismentioning
confidence: 99%